2023
DOI: 10.1111/aogs.14516
|View full text |Cite
|
Sign up to set email alerts
|

Association of postpartum medication practices with early breastfeeding cessation among mothers with chronic conditions: A prospective cohort study

Abstract: Introduction Use of medications is a common concern for breastfeeding women, particularly when they are strongly needed or unavoidable to manage maternal chronic conditions. Yet the influence of medication usage patterns on breastfeeding duration in mothers with chronic conditions is unclear. The objective of this study was to examine whether postpartum medication practices were associated with shorter breastfeeding duration or earlier than planned breastfeeding cessation among mothers with chronic conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Lactating women with a pre-existing chronic condition have a higher likelihood of medication use during lactation [ 16 ]. A very recent study conducted in Canada concluded that breastfeeding duration was significantly shorter for chronically ill women who discontinued their medications while breastfeeding, and their breastfeeding goals were less likely to be accomplished compared to women who continued to take their medicines [ 32 ]. Thus, future studies should particularly examine the impact of medication use due to chronic diseases on breastfeeding initiation, duration and cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Lactating women with a pre-existing chronic condition have a higher likelihood of medication use during lactation [ 16 ]. A very recent study conducted in Canada concluded that breastfeeding duration was significantly shorter for chronically ill women who discontinued their medications while breastfeeding, and their breastfeeding goals were less likely to be accomplished compared to women who continued to take their medicines [ 32 ]. Thus, future studies should particularly examine the impact of medication use due to chronic diseases on breastfeeding initiation, duration and cessation.…”
Section: Discussionmentioning
confidence: 99%